Kallikrein-like activity of crotalase, a snake venom enzyme that clots fibrinogen. - Markland, F S (1982)
During the amino acid sequence determination of crotalase (EC 3.4.21.30), the thrombin-like enzyme from the venom of Crotalus adamanteus (eastern diamondback rattlesnake), we found that, in addition to the expected structural homology with bovine thrombin (EC 3.4.21.5), there was even greater homology with porcine pancreatic kallikrein (EC 3.4.21.8). In exploring further the similarities between crotalase and kallikrein, several striking observations were made. First, crotalase was rapidly and specifically inhibited by the tripeptide affinity labeling derivative prolylphenylalanylarginine chloromethyl ketone, which is known to be a specific inhibitor of kallikrein. Second, NaDodSO4/acrylamide gel electrophoresis revealed that crotalase cleaves the plasma kallikrein-susceptible bonds in human high molecular weight kininogen, producing an intermediate with procoagulant activity. Crotalase-catalyzed cleavage of high molecular weight kininogen also liberates kinin as evidenced by rat blood pressure bioassay. Finally, crotalase exhibits substrate specificity not only for the thrombin chromogenic substrate S-2238 but also for the kallikrein substrates S-2302 and S-2266. Interestingly, one of the other reactions catalyzed by plasma kallikrein, the activation of plasminogen, was not one of the activities exhibited by crotalase.